Mapping of motor units in experimentally reinnervated rat muscle: Interpretation of histochemical and atrophic fibre patterns in neurogenic lesions - Kugelberg, Eric (1970)
The distribution of fibres in the motor units of reinnervated muscle is demonstrated. As shown in some experimental models, the histochemical and atrophic fibre patterns in neurogenic lesions are determined by the morphology of the specific motor units involved. This also helps to explain the alterations of motor unit action currents in neurogenic lesions.